2014
DOI: 10.12657/denbio.072.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rooting preparations on protein, chlorophyll and carotenoid content in leaves of Rosa gallica 'Duchesse d'Angoulême' cuttings

Abstract: Popularisation of historical rose cultivars is important for overall increase of biodiversity within currently available assortment, however their vegetative propagation is rather difficult. Possible scenario behind it is that commonly used one-bud leafy cuttings have limited storage capacity due to the small size of the stem. We hypothesised that the treatment of cuttings this rose with rooting preparations would positively affect on the condition of their leaves. We tested the effect of preparations based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 15 publications
6
29
0
Order By: Relevance
“…Monder, Niedzielski, and Woliński () and Monder and Pacholczak () evaluated the potential of biostimulants with hormone‐like activity for improving the viability of shrub rose cuttings. Shrub roses of older origin have a wide range of applications and are valuable for the preservation of biodiversity and historical heritage (Monder & Pacholczak, ).…”
Section: Biostimulant Effects On Ornamentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monder, Niedzielski, and Woliński () and Monder and Pacholczak () evaluated the potential of biostimulants with hormone‐like activity for improving the viability of shrub rose cuttings. Shrub roses of older origin have a wide range of applications and are valuable for the preservation of biodiversity and historical heritage (Monder & Pacholczak, ).…”
Section: Biostimulant Effects On Ornamentalsmentioning
confidence: 99%
“…Monder et al. () tested three environment‐friendly biostimulants based on seaweed extract (Bio Rhizotonic, Root Juice, and Bio Roots; Table ) and concluded that their use in optimal concentrations increased rooting ability and chlorophyll and protein contents in rose shoots. Monder and Pacholczak () studied whether the phenological phases of rose stock plants and the above‐mentioned biostimulants influenced the rhizogenesis of cuttings and changes in the content of polyphenolic acids.…”
Section: Biostimulant Effects On Ornamentalsmentioning
confidence: 99%
“…This preparation is recommended to stimulate root growth in plant production [15]. It has been shown that Root Juice used in rooting cuttings of the difficult-to-root Gallica rose 'Duchesse d' Angoulême' inhibited the ageing processes in leaves [16].…”
Section: Introductionmentioning
confidence: 99%
“…The process of rhizogenesis of historical roses by cuttings is considered to be rather long (10-12 weeks) and rooted cuttings are often of poor quality (Moroz, 2006;Monder et al, 2014;Nasri et al, 2015), especially when compared with modern roses, in which rhizogenesis lasts 4-6 weeks on the average (Costa et al, 2007;Pietrakowski, 2006;Wiśniewska-Grzeszkiewicz and Podwyszyńska, 2001). The rhizogenesis process in rose cuttings is known to be affected by many exogenous and endogenous factors, including the location in canopy (Hwnag et al, 2015), a type of cutting and a propagation date (Wiśniewska-Grzeszkiewicz and Podwyszyńska, 2001;Pietrakowski, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of the process of rhizogenesis lasting up to 10-12 weeks (Moroz, 2006;Monder et al, 2014) the single node leaf old rose cuttings are subjected to an extended period of stress conditions and precocious ageing processes. The cuttings of ground cover (Fuchs, 1986;Wiśniewska-Grzeszkiewicz and Podwyszyńska, 2001;Pietrakowski, 2006) and floribunda (Costa, 2002;Costa and Challa, 2002) roses have been rooted in 4-6 weeks.…”
Section: Introductionmentioning
confidence: 99%